What Drives the Swing Voter in Africa?. Issue 3 (9th April 2013) - Weghorst , Keith R.; Lindberg , Staffan I.
<x xml:space="preserve">Abstract</x> What makes African voters "up for grabs"? Existing approaches to the swing voter have several liabilities. This article introduces a new measure enabling a more comprehensive assessment of swing voting, including the differentiation between clientelistic and collective goods motivations. The issue of swing voting is then brought to an environment where voters are rarely considered persuadable: Africa. Using a count‐model estimation technique and original survey data from Ghana's critical 2008 elections, the analysis challenges the near consensus in African politics on clientelism as the only electoral strategy. When voters perceive politicians as providing collective, developmental goods, the efficacy of clientelism as a tool to win over voters is reduced. Many persuadable voters can also be won over by both clientelistic and collective goods, thus contradicting the literature presenting these as mutually exclusive. Finally, the analysis shows that incumbents do better when they provide collective goods even in highly clientelistic environments.